2022
DOI: 10.3390/s22010318
|View full text |Cite
|
Sign up to set email alerts
|

An FPGA-Embedded Brain-Computer Interface System to Support Individual Autonomy in Locked-In Individuals

Abstract: Brain-computer interfaces (BCI) can detect specific EEG patterns and translate them into control signals for external devices by providing people suffering from severe motor disabilities with an alternative/additional channel to communicate and interact with the outer world. Many EEG-based BCIs rely on the P300 event-related potentials, mainly because they require training times for the user relatively short and provide higher selection speed. This paper proposes a P300-based portable embedded BCI system reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Average power spectral densities, where X-axis is frequency (Hz); Y-axis is power spectral density (μV 2 of each frequency). Significant increases in theta (4-8 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20), and gamma (30-80 Hz) power were detected in the (C) cerebellum and (D) motor cortex of ataxia mice. Each dot represents average power spectral density per mouse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Average power spectral densities, where X-axis is frequency (Hz); Y-axis is power spectral density (μV 2 of each frequency). Significant increases in theta (4-8 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20), and gamma (30-80 Hz) power were detected in the (C) cerebellum and (D) motor cortex of ataxia mice. Each dot represents average power spectral density per mouse.…”
Section: Discussionmentioning
confidence: 99%
“…These EEG spectra were computed over 0-80 Hz frequency range at a resolution of 0.25 Hz (Figure 3A,B). Significant increases in theta (4-8 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20), and gamma (30-80 Hz) powers in both brain areas were detected in ataxia mice, while delta (0-4 Hz) and alpha (8-13 Hz) powers were unaffected in ataxia mice with or without DBS (Figure 3C,D). These data indicate that closed-loop DCN-DBS reduced movement-related EEG oscillatory activity and restored a baseline state cerebellocortical network.…”
Section: Fpga-based Closed-loop Dcn-dbs To Restore Motor Function And...mentioning
confidence: 93%
See 2 more Smart Citations
“…In [22] it is indicated that brain-computer interfaces are capable of detecting specific patterns and translate them into control signals for external devices by providing users suffering from serious motor-disabilities an alternative solution to communicate and interact with the world.…”
Section: Artificial Intelligencementioning
confidence: 99%

Domotics in inclusion and health: Descriptive Study

Montenegro Padilla,
Vélez Ipiales,
Gonzáles Bueno
et al. 2023
IDEAS